An TRIM59‐CDK6 axis regulates growth and metastasis of lung cancer. Issue 2 (4th December 2018) - Geng, Biao; Liang, Manman; qin, Lilong; Zhao, Wenying; wang, Hanli; wang, Lijing; pan, Xianhui; Chen, Xingwu
Abstract: Lung cancer (LC) is a devastating malignancy with no effective treatments, due to its complex genomic profile. Using bioinformatics analysis and immunohistochemical of lung carcinoma tissues, we show that TRIM59 as a critical oncoprotein relating to LC proliferation and metastasis. In this study, high TRIM59 expression was significantly correlated with lymph node metastasis, distant metastasis, and tumour stage. Furthermore, up‐regulation of TRIM59 expression correlated with poorer outcomes in LC patients. Mechanistically, TRIM59 play a key role in promoting LC growth and metastasis through regulation of extracellular‐signal regulated protein kinase (ERK) signalling pathway and epithelial‐to‐mesenchymal transition (EMT)‐markers, as validated by loss‐of‐function studies. In‐depth bioinformatics analysis showed that there is preliminary evidence of co‐expression of TRIM59 and cyclin dependent kinase 6 (CDK6) in LC. Notably, CDK6 expression significantly decreased when TRIM59 was knocked down in the LC cells. In contrast, exogenous up‐regulation of TRIM59 expression also induced significant increases in the expression of CDK6. Moreover, the expression of CDK6 was also inhibited by the ERK signalling inhibitor, U0126. The results of both loss‐ and gain‐of‐function studies showed that TRIM59 could regulate the expression of CDK6. Collectively, these data provide evidence that TRIM59 is involved in lung carcinoma growth and progression possibly through the induction of CDK6 expression and EMT process by activation of ERK pathway.